Editorial: effects of vildagliptin on GLP‐1 levels, gastric motor functions and food intake. A authors' reply. Issue 10 (23rd April 2019) - Masuy, Imke; Rotondo, Alessandra; Verbeure, Wout; Biesiekierski, Jessica R.; Deloose, Eveline; Tack, Jan
Abstract : Linked Content This article is linked to Rotondo et al and Camelleri papers. To view these articles, visithttps://doi.org/10.1111/apt.15195 andhttps://doi.org/10.1111/apt.15206 .